H5N1 and the Politics of Truth. (12th March 2013) - Bennett, Gaymon
Abstract: The social fact of disease means the ethical dimensions of H5N1 research are not only fraught but empirical. Any account of the reality of research that leaves out its ethical dimensions leaves out reality. For this reason alone—and quite apart from his carefully reasoned analysis—David Resnik deserves our thanks: his attention in this issue to the ethics of knowledge focuses our attention on the fact that the possible harms and benefits of H5N1 turn as much on the "politics of truth"—how work is conducted and talked about—as the biology itself. Sufficient discussion of this ethical dimension, as Resnik points out, requires attending to all stages of research, its premises and its ramifications. Resnik focuses on questions of publication and risk, offering philosophical, legal, and political insight. For my part, I would like to bolster (if complicate) Resnik's assessment by offering a few anthropological notes .